The Effect of Partial Defoliation, Leaf Position and Developmental Stage of the Vine on the Photosynthetic Activity of Vitis vinifera L. cv Cabernet Sauvignon - Hunter, J.J.; Visser, J.H. (South African Journal of Enology and Viticulture, 2017)
The effect of partial defoliation, :eaf position and developmental stage of the vine on the photosynthesis, stomatal resistance and transpiration of Vitis vinifera L. cv Cabernet Sauvignon was investigated. Partially defoliated vines displayed a higher rate of photosynthesis, generally increasing with degree of defoliation. The highest photosynthetic rates were found for the apical leaves, while those of the leaves opposite and below the bunches were restricted. Generally, rate of photosynthesis declined as the season progressed. The course of transpiration rate and stomata! resistance correlated with that of the rate of photosynthesis. However, transpiration and photosynthesis correlated poorly in the case of the apical leaves. In general, photon flux density and relative humidity at the leaf surface increased with an increase in defoliation percentage for all leaf positions. Leaf temperature was not significantly affected by partial defoliation. The results of the investigation suggested that excess vegetative growth is detrimental to interior-canopy microclimate as well as the photosynthetic rate of the entire vine. Partial defoliation seemed to provide a means to reduce some of the deleterious effects of vigorous growth.